THE VERSION OF THE NUMERICAL INTEGRATION IMPLICIT CIRCUITRY ON BASIS OF THE SHIFTED DIFFERENTIAL TRANSFORMATION - Ракушев, М. (Proceedings of National Aviation University (archive), 2012)
The implicit computing circuit of Cauchy problem solving for ordinary differential equation on the basis of the shifted differential transformations with using the power functions is offered. The developed circuit possesses the optimum order of accuracy and it is A-stable, which allows applying it for the solving of strict differential equations